2017
DOI: 10.18632/oncotarget.15071
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial protection from ischemia/reperfusion injury by exogenous galanin fragment

Abstract: Background and purpose: Galanin is a multifunctional neuropeptide with pleiotropic roles. The present study was designed to evaluate the potential effects of galanin (2-11) (G1) on functional and metabolic abnormalities in response to myocardial ischemia-reperfusion (I/R) injury. Experimental approach: Peptide G1 was synthesized by the 9-fluorenylmethoxycarbonyl (Fmoc)-based solid-phase method. The chemical structure was identified by

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
20
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 40 publications
2
20
0
5
Order By: Relevance
“…3 The N-terminal part is a fragment of galanin (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13) and the C-terminal part is the other bioactive dipeptide L-carnosine capable of scavenging hydroxyl radicals (Table 1). 6 A fragment of galanin (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13) contains residues Trp, 2 Asn, 5 Gly 8 and Tyr, 9 which are necessary for interaction of the peptide with the GalR2 receptor 7,8 and thereby to trigger cardioprotective effects. L-carnosine tailing to C-terminal part of peptide G1 enhances its resistance to the action of exopeptidases due to the insertion of βAla14.…”
Section: Structure and Properties F Of Peptide G1mentioning
confidence: 99%
See 3 more Smart Citations
“…3 The N-terminal part is a fragment of galanin (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13) and the C-terminal part is the other bioactive dipeptide L-carnosine capable of scavenging hydroxyl radicals (Table 1). 6 A fragment of galanin (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13) contains residues Trp, 2 Asn, 5 Gly 8 and Tyr, 9 which are necessary for interaction of the peptide with the GalR2 receptor 7,8 and thereby to trigger cardioprotective effects. L-carnosine tailing to C-terminal part of peptide G1 enhances its resistance to the action of exopeptidases due to the insertion of βAla14.…”
Section: Structure and Properties F Of Peptide G1mentioning
confidence: 99%
“…24 The shift in the balance between ROS formation and antioxidant protection in favour of the first leads to redox imbalance, oxidative stress and an increase in cell damage. A loss of antioxidant enzymes activities in our experiments could be associated with both the harmful effects of ROS and leakage of antioxidant enzymes into the extracellular fluid.It was previously shown that treatment of rat myocardial H9C2 cells with galanin fragments (2-11) and (2-15) significantly reduced mitochondrial superoxide production in response to oxidative stress 4,5. Intravenous administration of full-length galanin to mice with myocardial I/R injury caused a similar effect 25.…”
mentioning
confidence: 92%
See 2 more Smart Citations
“…Cardiomyocyte death due to ischemia/reperfusion (I/R) injury is well-known to increase morbidity, mortality and medical cost in patients with ischemic heart disease [1][2][3][4]. Treatment for this myocardial ischemia-reperfusion disorder and cardiomyocyte death has had limited success.…”
Section: Introductionmentioning
confidence: 99%